Racial/Ethnic Disparities in Financial Hardship During the First Year of the Pandemic (Mary Ann Liebert, 2023)
Introduction: The economic impact of the COVID-19 pandemic has been substantial, yet little is known about the financial effects resulting from lost employment or financial hardship racial?ethnic disparities. Methods: We conducted a nationally representative, online survey of 5500 English- and Spanish-speaking American Indian/Alaska Native, Asian, Black/African American, Native Hawaiian/Pacific Islander, Latino, White, and multiracial adults, from December 2020 to February 2021. Six financial hardship domains were measured (lost income, debt, unmet expenses, unmet health care expenses, housing insecurity, and food insecurity). Prevalence of financial hardship among each racial-ethnic group was estimated using multivariable Poisson regression. Results: Overall, 70.3% reported experiencing financial hardship; debt (57.6%), lost income (44.5%), and unmet expenses (33.7%) were most common. American Indian/Alaska Native (adjusted prevalence ratio [aPR]=1.19, 95% confidence interval [CI]=1.04 to 1.35), Black/African American (aPR=1.18, 95% CI=1.06 to 1.32), Latino (English-speaking: aPR=1.15, 95% CI=1.01 to 1.31; Spanish-speaking: aPR=1.27, 95% CI=1.12 to 1.45), and Native Hawaiian/Pacific Islander (aPR=1.21, 95% CI=1.06 to 1.38) adults were more likely to experience financial hardship, compared with White adults. American Indian/Alaska Native, Black/African American, Spanish-speaking Latino, and Native Hawaiian/Pacific Islander adults were also more likely to report hardship in almost all hardship domains (e.g., housing insecurity: aPRs=1.37?1.91). Conclusions: Racial/ethnic minorities were more likely to experience financial hardship during the pandemic. The prevalence of lost income was similar across most racial/ethnic groups, suggesting that preexisting wealth disparities led to some groups being less able to handle the economic shocks caused by the COVID-19 pandemic. Financial hardship may be underestimated for communities without English or Spanish fluency. Without intervention, financial hardship will likely exacerbate wealth disparities in the United States.